Adsorption heat storage material with multi-stage stepped pore structure and preparation method of adsorption heat storage material
By introducing a multi-stage cascade pore structure into the adsorption heat storage material, combining metal foams with different porosities and multi-stage pore coatings, the problems of poor thermal conductivity and limited adsorbent diffusion in the prior art are solved, and efficient thermal energy storage and release are achieved.
Patent Information
- Application Number
- CN202411752748.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing adsorption and heat storage materials have poor thermal conductivity and limited diffusion of adsorbents, resulting in slow heat storage and heat release speed, making it difficult to apply to rapid thermal energy transfer scenarios.
Adsorption heat storage materials with multi-stage pore structures are used to introduce metal foam layers with different porosities into the metal foam matrix and apply adsorbent coatings containing multi-stage pores on their surfaces to optimize the pore structure of the material, reduce thermal resistance and improve the diffusion speed of adsorbent.
It significantly improves the thermal energy storage and release rate, meets the application needs of rapid thermal energy storage and release, and simplifies the preparation process and reduces costs.
Smart Images

Figure CN119592308A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high-efficiency energy storage, and relates to the preparation of adsorption heat storage materials, and more specifically to an adsorption heat storage material with a multi-level stepped pore structure and a preparation method thereof. The material is prepared by combining metal foams of different porosities and coating an adsorbent coating containing multi-level pores on its surface, aiming to improve the efficiency of thermal energy storage and release, and solve the problem of poor heat and mass transfer performance of traditional adsorption heat storage materials. Background Art
[0002] Due to the extensive use of traditional fossil energy, energy and environmental issues are becoming increasingly severe, and energy conservation, emission reduction and increasing the utilization rate of renewable energy are extremely urgent. In energy utilization, heat supply accounts for a high proportion of terminal energy consumption, so it is extremely necessary to achieve clean and low-carbon heating technology. By collecting as much industrial waste heat and renewable energy as possible through efficient thermal storage technology, it is expected to solve the problem of time and space mismatch between heat supply and demand, and provide clean heat for industry and construction.
[0003] Adsorption Thermal Energy Storage achieves the storage and release of thermal energy through the reversible adsorption and desorption process of solid porous adsorbents and working fluids such as water vapor or ammonia. It has significant advantages such as high thermal storage density and low heat loss, and has broad application prospects. This technology can efficiently collect industrial waste heat and renewable energy (such as solar energy and geothermal energy) and realize the temporal and spatial transfer of thermal energy. It has potential value in the fields of building heating, industrial waste heat recovery and mobile energy systems.
[0004] However, despite its great potential for adsorption heat storage, it also has many problems. For example, the solid porous adsorbents commonly used for adsorption heat storage (such as zeolite, silica gel, molecular sieves and alumina) usually have a low thermal conductivity of only 0.1-0.3 W / K·m. This low thermal conductivity leads to a slow heat transfer rate of the thermal storage material, thereby prolonging the storage and release time of thermal energy, greatly limiting its application in rapid thermal energy transfer scenarios. In addition, the pores inside the existing porous adsorbents are mostly nanoscale micropores, and their pore diameters are usually less than 2 nanometers. Although this structure has the advantage of providing a larger specific surface area, the adsorption and diffusion rate of the adsorbed working fluid inside it is slow, which limits the migration rate of the working fluid inside the adsorbent, and also leads to a slow heat storage and release process, making it difficult to apply to scenarios of rapid storage and release of thermal energy.
[0005] At present, the improvement of adsorbent structure is usually achieved by adding high thermal conductivity materials (such as graphene, metal particles, etc.) to the adsorbent, or pressing the powder / granular adsorbent into thin sheets to improve its thermal conductivity and adsorption rate. However, since the above methods only improve the local thermal conductivity and do not fundamentally change the pore size of the adsorbent, the internal diffusion resistance of the adsorbent is not reduced, and the thermal resistance between adsorbent particles, between adsorbent and high thermal conductivity materials, and between adsorbent and heating source is still huge, and the tableting process may cause partial loss of adsorption performance and affect its actual effect. Therefore, the existing improved adsorbents cannot meet the application scenarios of rapid heat storage, and there is still a lot of room for improvement. In addition, the preparation process of traditional adsorbents usually requires complex processes and high costs. In order to optimize the performance of the adsorbent, it is often necessary to introduce a variety of additives (such as binders, templates, etc.) and undergo multiple complex treatment processes (such as high-temperature calcination, ultrasonic dispersion, etc.). Although this method can improve the performance of the adsorbent to a certain extent, the complexity of the preparation process and the increase in cost limit its feasibility of large-scale promotion.
[0006] In summary, adsorption thermal storage materials have significant limitations in terms of heat and mass transfer performance, structural design and preparation process, which limits their application in the field of rapid thermal energy storage and release. How to effectively improve the thermal conductivity and adsorption performance of adsorption thermal storage materials, optimize their pore structure design, simplify the preparation process and reduce costs have become technical problems that need to be solved urgently. These technical improvements are of great significance to promoting the application of adsorption thermal storage technology in the fields of clean energy and industrial energy conservation. Summary of the invention
[0007] 1. Purpose of the invention In view of the defects and shortcomings of the adsorption heat storage materials in the prior art, such as poor thermal conductivity, limited diffusion of adsorbents, and slow heat storage and release speed, in order to solve at least one of the above and other technical problems in the prior art, the purpose of the present invention is to provide an adsorption heat storage material with multi-level stepped pores for adsorption heat storage and a preparation method thereof, by introducing metal foams of different porosities into the adsorption heat storage material, adopting a multi-level stepped pore structure composed of metal foams of different porosities, and coating an adsorbent coating containing macropores, mesopores and micropores to optimize the pore structure of the material, significantly reducing the thermal resistance inside the material, and increasing the diffusion rate of the adsorbent, and significantly improving the heat storage and release rate. The invention enhances the thermal conductivity of the material by reasonably designing the porosity gradient of the metal foam, and by coating a multi-level pore coating, improves the adsorption and desorption efficiency of the adsorbent, greatly improves the heat storage and release rate, thereby realizing a wide range of applications in the application scenarios of rapid heat storage and release. This technical solution not only improves the performance of the adsorption heat storage material, but also simplifies the preparation process of the material, and has a good practical application prospect.
[0008] (II) Technical solution In order to achieve the purpose of the invention and solve the technical problems, the present invention adopts the following technical solutions: The first invention object of the present invention is to provide an adsorption heat storage material with a multi-level stepped pore structure, which is used to achieve efficient storage and rapid release of thermal energy, especially to provide excellent performance in the application scenario of rapid thermal energy storage and release, and at least comprises a metal foam matrix and an adsorbent coating, wherein: The metal foam matrix is used to conduct heat energy and provide structural support, and includes at least multiple layers of metal foam layers with different porosities, the thermal conductivity of the metal foam material in each layer is not less than 0.5 W / m·K, and the porosity of the multiple layers of metal foam layers increases step by step along the heat source direction, the metal foam layer closest to the heat source has the smallest porosity, and its porosity is controlled within the range of 30% to 50%, so as to optimize the conduction efficiency of heat energy and reduce thermal resistance, the metal foam layer farthest from the heat source has the largest porosity, and its porosity is controlled within the range of 60% to 85%, so as to increase the diffusion rate of the adsorbate and enhance the adsorption capacity, the porosity of each layer of metal foam material is controlled by accurately adjusting the manufacturing process of the metal foam to ensure that the conduction and diffusion of heat energy between different layers are balanced, and adjacent metal foam layers are connected by welding at the interface joint to form a stable multilayer structure, so as to ensure the mechanical stability and thermal conductivity of the metal foam matrix under high temperature and multiple thermal cycle conditions; The adsorbent coating is used to adsorb and release the working fluid and is uniformly coated on the surface of the metal foam substrate, and its overall thickness is controlled within the range of 100-1000 μm to ensure that the coating has good adsorption capacity and heat transfer performance, and the adsorbent coating is structurally formed into a multi-level pore structure composed of a large number of macropores, mesopores and micropores to facilitate accelerating the diffusion rate of the adsorbate and improving the adsorption and desorption efficiency, wherein: the pore size range of the macropores is controlled within 50-200 nm to promote the rapid diffusion of the working fluid and the rapid transfer of heat, the pore size range of the mesopores is controlled within 2-50 nm to provide a larger specific surface area and enhance the adsorption capacity, and the pore size of the micropores is controlled to be less than 2 nm to improve the adsorption density and storage capacity of the adsorbate; The combination of the metal foam matrix and the adsorbent coating enables the prepared adsorption heat storage material to have efficient heat conduction and adsorption performance during the heat storage and release process. The thermal resistance is effectively reduced by the stepped pore structure of the metal foam matrix, and the diffusion rate of the adsorbate is increased by the multi-level pore structure in the adsorbent coating, thereby improving the thermal energy storage and release efficiency of the adsorption heat storage material and meeting the application requirements of rapid thermal energy storage and release.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned adsorption heat storage material with a multi-step pore structure, wherein the preparation method comprises at least the following steps: SS1. Preparation of metal foam matrix 2 to 5 metal foam layers with different porosities are selected, and the thermal conductivity of the metal foam material in each metal foam layer is not less than 0.5 W / m·K. The selected metal foam layers are arranged from bottom to top according to the porosity from small to large to form a stepped pore structure, wherein the porosity of the bottom metal foam layer is the smallest, and its porosity is controlled within the range of 30% to 50%, and the porosity of the top metal foam layer is the largest, and its porosity is controlled within the range of 60% to 85%, and the adjacent metal foam layers are connected by welding at the interface joint to form a stable multilayer structure; SS2. Cleaning and drying of metal foam substrates The metal foam substrate prepared in step SS1 is cleaned by using an organic solvent and deionized water in combination with ultrasonic cleaning or pickling to remove impurities, oil stains and oxides attached to the surface of the metal foam substrate, and then dried at a temperature of 60 to 80° C. for 2 to 10 hours to ensure that there is no moisture and organic residue on the surface of the metal foam substrate, thereby obtaining a clean and dry metal foam substrate for standby use; SS3. Preparation of Adsorbent Coating Slurry The adsorbent, deionized water, binder and pore-forming agent are mixed into slurry in a suitable proportion, and the proportion of the slurry is optimized and determined according to experimental data to ensure that the adsorbent particles are evenly distributed and the binding force between the binder and the adsorbent is moderate, wherein the adsorbent is selected from at least one of zeolite, silica gel, alumina and molecular sieve, the binder is selected from at least one of silica sol, aluminum sol, titanium sol, silicone resin, yellow dextrin and sesbania powder, and the pore-forming agent is selected from at least one of cellulose, nanographite flakes, ammonium bicarbonate and acrylic resin, and after mixing to obtain the slurry, the slurry is ground in a rubber mill for 1 to 3 hours to homogenize the slurry components and improve the particle refinement, so as to ensure that the average particle size of the slurry is controlled within the range of 30 to 50 nm; SS4. Application of Adsorbent Coating The prepared slurry is uniformly coated on the surface of the metal foam substrate obtained in step SS2 by dipping or spraying. When the dipping process is adopted, the metal foam substrate is immersed in the slurry to ensure uniform coating of the coating. When the spraying process is adopted, the slurry is sprayed onto the surface of the metal foam substrate using a special spray gun to ensure uniform coating thickness, and the coating is formed after drying and curing at 70-90°C. The coating is applied once or multiple times until the required coating thickness is reached, and the overall coating thickness is controlled to be 100-1000 μm; SS5. Calcination of adsorbent coating The metal foam substrate coated with the adsorbent coating is calcined at a temperature of 500-600°C for 1-6 hours to remove the organic solvent, moisture and pore-forming agent in the adsorbent coating, so as to form a multi-level pore structure containing a large number of micropores, mesopores and macropores in the adsorbent coating, thereby obtaining an adsorption heat storage material with a multi-level stepped pore structure; SS6. Performance test of adsorption heat storage materials (optimization steps) The prepared adsorption heat storage material was subjected to performance tests, including the determination of the thermal conductivity, adsorption capacity and adsorption rate of the material. The thermal conductivity test was carried out using the transient plane heat source method and the test temperature was 30°C. The adsorption performance test was carried out under standard test conditions of 1.27 kPa water partial pressure and 30°C temperature. The change in adsorption amount within 60 minutes was recorded to ensure that the water vapor adsorption capacity of the prepared adsorption heat storage material was not less than 0.35 g / g, the average adsorption rate was not less than 1.2 g / min, and the thermal conductivity was not less than 0.85 W / m·K.
[0010] (III) Technical Effect Compared with the prior art, the adsorption heat storage material with multi-level stepped pores and the preparation method thereof of the present invention have the following beneficial and significant technical effects: (1) By utilizing the preparation method of the adsorption heat storage material with multi-level stepped pores provided by the present invention, an adsorption heat storage material with good adsorption performance can be prepared through innovative design and production process. The material can significantly improve the heat and mass transfer performance of the heat storage process, greatly increase the heat energy storage and release rate, reduce the preparation cost, and has efficient and stable heat energy conversion capabilities.
[0011] (2) The adsorption heat storage material with stepped pores provided by the present invention, by arranging metal foams with gradually increasing porosity along the direction of the heat source, reduces thermal resistance while enabling the adsorbate to quickly reach the bottom along the stepped pores, thereby increasing the adsorption speed. In particular, the bottom metal foam layer with a smaller porosity ensures that heat is quickly transferred to the farther layers through a lower thermal resistance, while the upper metal foam layer with a larger porosity provides more space for the adsorbate to diffuse, thereby significantly improving the efficiency and speed of thermal energy storage and release. This design not only optimizes the thermal conductivity performance, but also increases the transmission path of the adsorbate, effectively shortening the time of thermal energy storage and release.
[0012] (3) The adsorption heat storage material with multi-level pores provided by the present invention is coated with an adsorption material mixture containing a template, and after drying and calcination, a multi-level pore coating containing a large number of macropores, mesopores and micropores is obtained on the surface of the metal foam. Compared with simple microporous adsorbents, the multi-level pore structure not only greatly increases the specific surface area, but also greatly increases the adsorption and diffusion rate of the adsorbent. Macropores and mesopores help accelerate the entry and desorption process of the adsorbate, while micropores increase the adsorption density and storage capacity. Through the design of this multi-level pore structure, the diffusion rate of the adsorbate is significantly improved, thereby enhancing the adsorption capacity and heat storage capacity of the material.
[0013] (4) The method for preparing an adsorption heat storage material with multi-level stepped pores provided by the present invention can efficiently prepare an adsorption heat storage material with rapid heat storage and release capabilities by splicing a plurality of metal foam layers with different porosities and coating, drying, and calcining the adsorbent. In addition, through the calcination treatment, the organic solvent and moisture in the adsorbent coating are effectively removed, and the pore-forming agent in the coating is also processed to form a multi-level pore network with a high-strength structure. This multi-level pore structure not only enhances the adsorption performance of the adsorbent, but also improves the thermal stability of the material. The metal foam substrate and the coating are firmly bonded and can maintain stability during high temperatures and multiple thermal cycles, avoiding coating peeling or performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic diagram of the arrangement of multiple metal foam layers in the adsorption heat storage material of the present invention; Figure 2 It is a schematic diagram of an adsorbent coating with multi-level pores in the adsorption heat storage material of the present invention; Figure 3 It is a flow chart for preparing the adsorption heat storage material with multi-level stepped pores of the present invention. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the technical scheme in the embodiment of the present invention will be described in more detail below in conjunction with the drawings in the embodiment of the present invention. The described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present invention, and should not be understood as limiting the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0016] The present invention aims to provide an adsorption heat storage material with multi-step pores for adsorption heat storage and a preparation method thereof. By introducing metal foams with different porosities into the adsorption heat storage material, a multi-step pore structure composed of metal foams with different porosities is adopted, and an adsorbent coating containing macropores, mesopores and micropores is coated to optimize the pore structure of the material, significantly reduce the thermal resistance inside the material, increase the diffusion rate of the adsorbate, and significantly improve the thermal energy storage and release rate.
[0017] Example 1 As a specific example, Figure 1 , 2 As shown, the adsorption heat storage material with multi-level stepped pores provided by the present invention comprises a metal foam substrate 10 and an adsorbent coating 20, wherein the metal foam substrate 10 is used to conduct heat energy and provide structural support, such as Figure 1 As shown, it includes multiple layers (for example, 2 to 5 layers, and the figure shows a case of 3 layers) of metal foam layers 11 to 13 with different porosities, the thermal conductivity of the metal foam material in each layer is not less than 0.5 W / m·K, and the porosity of the multiple metal foam layers 11 to 13 increases step by step along the heat source direction, the metal foam layer 13 closest to the heat source has the smallest porosity, and its porosity is controlled in the range of 30% to 50% to optimize the conduction efficiency of heat energy and reduce thermal resistance, the metal foam layer 11 farthest from the heat source has the largest porosity, and its porosity is controlled in the range of 60% to 85% to increase the diffusion rate of the adsorbate and enhance the adsorption capacity, the porosity range of the middle metal foam layer 12 is in the transition range, the porosity control of each layer of metal foam material is achieved by accurately adjusting the manufacturing process of the metal foam to ensure that the conduction and diffusion of heat energy between different layers are balanced, and the adjacent metal foam layers are connected by welding at the interface to form a stable multilayer structure, ensuring the mechanical stability and thermal conductivity of the metal foam matrix under high temperature and multiple thermal cycles.
[0018] Preferably, the metal foam matrix 10 is composed of 2-5 metal foam layers with different porosities. The metal foam material in each metal foam layer can be one or more combinations of foamed copper, foamed aluminum, foamed nickel, foamed iron, and foamed titanium. The porosity of each metal foam layer is precisely controlled by adjusting the manufacturing process of the metal foam material, including adjusting the type and addition amount of the foaming agent, controlling the melting temperature of the metal foam, and the foam generation time, so as to achieve porosity control of each layer of metal foam material and ensure that the junction of metal foam layers with different porosities has good mechanical stability and thermal conductivity.
[0019] In addition, the porosity difference in each layer of metal foam material of the metal foam matrix 10 is achieved by controlling the gas release rate and cooling rate during the foam metal forming process, and specifically by accelerating the gas release rate to increase the foam porosity, and by slowly cooling to reduce the porosity of the foam metal, ultimately achieving a porosity gradient that increases step by step along the heat source direction.
[0020] Preferably, the multi-layer structure of the metal foam matrix 10 adopts a step-by-step welding or brazing process, so that the bonding between the layers of metal foam materials is not only physically stable but also has good continuity in thermal conduction, thereby making the heat transfer in the metal foam matrix more efficient, effectively reducing heat loss and improving the thermal response speed of the material.
[0021] like Figure 2 As shown, the adsorbent coating 20 is used to adsorb and release thermal energy working fluid and is uniformly coated on the surface of the metal foam substrate. Its overall thickness is controlled within the range of 100-1000 μm to ensure that the coating has good adsorption capacity and heat transfer performance, and the adsorbent coating 20 is structurally formed into a multi-level pore structure composed of a large number of macropores, mesopores and micropores to accelerate the diffusion rate of the adsorbate and improve the adsorption and desorption efficiency, wherein the pore size range of the macropores is controlled within 50-200 nm to promote the rapid diffusion of the working fluid and the rapid transfer of heat, the pore size range of the mesopores is controlled within 2-50 nm to provide a larger specific surface area and enhance the adsorption capacity, and the pore size of the micropores is controlled to be less than 2 nm to improve the adsorption density and storage capacity of the adsorbate.
[0022] Preferably, the adsorbent coating 20 is composed of an adsorbent, a binder and a pore-forming agent, wherein the adsorbent can be one or more combinations of zeolite, silica gel, alumina, and molecular sieves, the binder is selected from one or more combinations of silica sol, aluminum sol, titanium sol, silicone resin, yellow dextrin, and sesbania powder, and the pore-forming agent is selected from one or more combinations of cellulose, nanographite sheets, ammonium bicarbonate, and acrylic resin. The components are reasonably proportioned to ensure the adsorption performance and structural stability of the coating.
[0023] The adsorption heat storage material with multi-level stepped pores provided by the present invention, the combination of the metal foam matrix 10 and the adsorbent coating 20 makes the prepared adsorption heat storage material have efficient heat conduction and adsorption performance during heat storage and heat release. The stepped pore structure of the metal foam matrix effectively reduces the thermal resistance, and the multi-level pore structure in the adsorbent coating increases the diffusion rate of the adsorbate, thereby improving the thermal energy storage and release efficiency of the adsorption heat storage material, and meeting the application requirements of rapid storage and release of thermal energy.
[0024] Example 2 Based on the above-mentioned Example 1, this Example 2 further describes in detail the preparation method of the adsorption heat storage material with multi-level stepped pores of the present invention. Figure 3 As shown, the method includes: SS1. Preparation of metal foam matrix 2 to 5 metal foam layers with different porosities are selected, and the thermal conductivity of the metal foam material in each metal foam layer is not less than 0.5 W / m·K. The selected metal foam layers are arranged from bottom to top according to the porosity from small to large to form a stepped pore structure, wherein the porosity of the bottom metal foam layer is the smallest, and its porosity is controlled within the range of 30% to 50%, and the porosity of the top metal foam layer is the largest, and its porosity is controlled within the range of 60% to 85%, and the adjacent metal foam layers are connected by welding at the interface joint to form a stable multilayer structure; Preferably, when forming each metal foam layer, the metal material is heated to a molten state, and the foaming process of the molten metal, the amount of foaming agent added and the foam cooling rate are controlled to form metal foams with different porosities; and the thickness of each metal foam layer can be adjusted according to actual application requirements and controlled within the range of 10 to 50 mm, and the porosity difference between adjacent metal foam layers is controlled within the range of 5% to 15% to achieve optimal heat conduction and material transfer effects.
[0025] SS2. Cleaning and drying of metal foam substrates The metal foam substrate prepared in step SS1 is cleaned by using an organic solvent and deionized water in combination with ultrasonic cleaning or pickling to remove impurities, oil stains and oxides attached to the surface of the metal foam substrate, and then dried at a temperature of 60 to 80° C. for 2 to 10 hours to ensure that there is no moisture and organic residue on the surface of the metal foam substrate, thereby obtaining a clean and dry metal foam substrate for standby use; Preferably, acetone is selected as the organic solvent. The cleaning process includes immersing the metal foam substrate in acetone and deionized water for 3 times respectively, with each immersion time being not less than 10 minutes, and ultrasonic cleaning is performed to improve the cleaning effect. The drying process is carried out in a vacuum drying oven at 60-80°C and a pressure not higher than 0.1 MPa to ensure that the moisture and organic solvent residues in the internal pores of the metal foam substrate are fully removed, thereby providing a clean substrate for subsequent coatings.
[0026] SS3. Preparation of Adsorbent Coating Slurry The adsorbent, deionized water, binder and pore-forming agent are mixed into slurry in a suitable proportion, and the proportion of the slurry is optimized and determined according to experimental data to ensure that the adsorbent particles are evenly distributed and the binding force between the binder and the adsorbent is moderate, wherein the adsorbent is selected from at least one of zeolite, silica gel, alumina and molecular sieve, the binder is selected from at least one of silica sol, aluminum sol, titanium sol, silicone resin, yellow dextrin and sesbania powder, and the pore-forming agent is selected from at least one of cellulose, nanographite flakes, ammonium bicarbonate and acrylic resin, and after mixing to obtain the slurry, the slurry is ground in a rubber mill for 1 to 3 hours to homogenize the slurry components and improve the particle refinement, so as to ensure that the average particle size of the slurry is controlled within the range of 30 to 50 nm; Preferably, the mass ratio of the adsorbent, deionized water, binder and pore-forming agent is 1:1:0.1~0.2:0.02~0.1, wherein the adsorbent is 13X molecular sieve, the binder is silica sol, and the pore-forming agent is cellulose; during the slurry preparation process, the adsorbent and deionized water are first mixed and stirred for 30 minutes, and then the binder is added and stirred for 30 minutes, and finally the pore-forming agent is added and stirred evenly; after mixing to obtain the slurry, it is ground at a speed of 300~500 rpm for 2 hours to ensure the uniformity and stability of the slurry.
[0027] SS4. Application of Adsorbent Coating The prepared slurry is uniformly coated on the surface of the metal foam substrate obtained in step SS2 by dipping or spraying. When the dipping process is adopted, the metal foam substrate is immersed in the slurry to ensure uniform coating of the coating. When the spraying process is adopted, the slurry is sprayed onto the surface of the metal foam substrate using a special spray gun to ensure uniform coating thickness, and the coating is formed after drying and curing at 70-90°C. The coating is applied once or multiple times until the required coating thickness is reached, and the overall coating thickness is controlled to be 100-1000 μm; Preferably, the coating is carried out by spraying, using a pneumatic spray gun, the spraying pressure is controlled at 0.2~0.3 MPa, and the spraying distance is maintained at 15~20 cm; after each spraying, it is dried at 80°C for 30 minutes, and the spraying is repeated 3~5 times to achieve the desired coating thickness; after the last spraying, it is pre-cured at 85°C for 2 hours, and then post-cured at 120°C for 1 hour to ensure the bonding strength between the coating and the metal foam substrate; the final thickness of the coating is controlled at 300±50 μm.
[0028] SS5. Calcination of adsorbent coating The metal foam substrate coated with the adsorbent coating is calcined at a temperature of 500-600 °C for 1-6 hours. The organic solvent, moisture and pore-forming agent in the adsorbent coating are removed by the calcination treatment to form a multi-level pore structure containing a large number of micropores, mesopores and macropores in the adsorbent coating, thereby obtaining an adsorption heat storage material with a multi-level stepped pore structure.
[0029] Preferably, the calcination process adopts a programmed temperature rising method, with the temperature rising from room temperature to 300°C at a heating rate of 2°C / min and keeping it for 1 hour to remove residual moisture, then rising to 400°C and keeping it for 1 hour to decompose organic matter, and finally rising to 550°C and keeping it for 3 hours to completely remove the pore-forming agent and form a stable multi-level pore structure. The cooling process adopts natural cooling, and the cooling rate does not exceed 5°C / min to avoid cracking or falling off of the coating due to thermal stress.
[0030] SS6. Performance test of adsorption heat storage materials (optimization steps) The prepared adsorption heat storage material was subjected to performance tests, including the determination of the thermal conductivity, adsorption capacity and adsorption rate of the material. The thermal conductivity test was carried out using the transient plane heat source method and the test temperature was 30°C. The adsorption performance test was carried out under standard test conditions of 1.27 kPa water partial pressure and 30°C temperature. The change in adsorption amount within 60 minutes was recorded to ensure that the water vapor adsorption capacity of the prepared adsorption heat storage material was not less than 0.35 g / g, the average adsorption rate was not less than 1.2 g / min, and the thermal conductivity was not less than 0.85 W / m·K to meet the actual application requirements.
[0031] Technical effect verification: Example: Based on the preparation method shown in Example 2 above, three types of copper foams (all with a size of 50*50*5mm) with porosities of 50%, 75% and 95% were arranged from bottom to top according to the porosity from small to large, connected by welding at the joints, washed with acetone and deionized water for 3 times respectively, and then dried at 80°C for 6 hours. 13X molecular sieve adsorbent, deionized water, silica sol, and cellulose were mixed in a mass ratio of 1:1:0.2:0.1, and ground in a rubber mill for 2 hours to obtain a slurry, which was sprayed on the metal foam assembly, and then dried and solidified at 90°C, and sprayed repeatedly for 3 times, so that the average thickness of the coating on the metal foam reached 300 microns, and calcined at 600°C for 3 hours to remove the pore-forming agent, to obtain an adsorption heat storage material with multi-level stepped pores.
[0032] Comparative example: A copper foam with a porosity of 75% (size of 50*50*15mm) was washed 3 times with acetone and deionized water respectively, and then dried at 80°C for 6 hours. A 13X molecular sieve adsorbent, deionized water, and silica sol were mixed in a mass ratio of 1:1:0.2, and ground in a rubber mill for 2 hours to obtain a slurry, which was sprayed on the metal foam assembly, and then dried and cured at 90°C. The spraying was repeated 3 times, so that the average thickness of the coating on the metal foam reached 300 microns, and it was calcined at 600°C for 3 hours to obtain a comparative adsorption heat storage material.
[0033] Comparison of test results: Under the conditions of 1.27 kPa water partial pressure and 30°C temperature, the water adsorption amount, average adsorption rate and thermal conductivity of the adsorption heat storage materials obtained in the embodiment and the comparative example were tested. The results are shown in Table 1. It can be seen that the adsorption rate and thermal conductivity of the embodiment of the present invention are significantly higher than those of the comparative example.
[0034] Table 1 Through the above embodiments, the purpose of the present invention is fully and effectively achieved. Those skilled in the art can understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Although the present invention has been described with respect to the most practical and preferred embodiments currently considered, it should be understood that the present invention is not limited to the disclosed embodiments, and any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. An adsorption heat storage material with a multi-level stepped pore structure, used to achieve efficient storage and rapid release of thermal energy, comprising at least a metal foam matrix and an adsorbent coating, characterized in that: The metal foam matrix is used to conduct heat energy and provide structural support, and includes at least multiple layers of metal foam layers with different porosities, the thermal conductivity of the metal foam material in each layer is not less than 0.5 W / m·K, and the porosity of the multiple layers of metal foam layers increases step by step along the heat source direction, the metal foam layer closest to the heat source has the smallest porosity, and its porosity is controlled within the range of 30% to 50%, so as to optimize the conduction efficiency of heat energy and reduce thermal resistance, the metal foam layer farthest from the heat source has the largest porosity, and its porosity is controlled within the range of 60% to 85%, so as to increase the diffusion rate of the adsorbate and enhance the adsorption capacity, the porosity of each layer of metal foam material is controlled by accurately adjusting the manufacturing process of the metal foam to ensure that the conduction and diffusion of heat energy between different layers are balanced, and adjacent metal foam layers are connected by welding at the interface joint to form a stable multilayer structure, so as to ensure the mechanical stability and thermal conductivity of the metal foam matrix under high temperature and multiple thermal cycle conditions; The adsorbent coating is used to adsorb and release the working fluid and is uniformly coated on the surface of the metal foam substrate, and its overall thickness is controlled within the range of 100-1000 μm to ensure that the coating has good adsorption capacity and heat transfer performance, and the adsorbent coating is structurally formed into a multi-level pore structure composed of a large number of macropores, mesopores and micropores to facilitate accelerating the diffusion rate of the adsorbate and improving the adsorption and desorption efficiency, wherein: the pore size range of the macropores is controlled within 50-200 nm to promote the rapid diffusion of the working fluid and the rapid transfer of heat, the pore size range of the mesopores is controlled within 2-50 nm to provide a larger specific surface area and enhance the adsorption capacity, and the pore size of the micropores is controlled to be less than 2 nm to improve the adsorption density and storage capacity of the adsorbate; The combination of the metal foam matrix and the adsorbent coating enables the prepared adsorption heat storage material to have efficient heat conduction and adsorption performance during the heat storage and heat release process. The thermal resistance is effectively reduced through the stepped pore structure of the metal foam matrix, and the diffusion rate of the adsorbate is increased through the multi-level pore structure in the adsorbent coating, thereby improving the thermal energy storage and release efficiency of the adsorption heat storage material.
2. The adsorption heat storage material with a multi-level stepped pore structure according to claim 1, characterized in that: The metal foam matrix is composed of 2-5 metal foam layers with different porosities. The metal foam material in each metal foam layer is one or more combinations of foam copper, foam aluminum, foam nickel, foam iron, and foam titanium. The porosity of each metal foam layer is precisely controlled by adjusting the manufacturing process of the metal foam material, including adjusting the type and addition amount of the foaming agent, controlling the melting temperature of the metal foam, and the foam generation time, so as to achieve porosity control of each layer of metal foam material and ensure that the junction of metal foam layers with different porosities has good mechanical stability and thermal conductivity.
3. The adsorption heat storage material with a multi-level stepped pore structure according to claim 2, characterized in that: The porosity difference in each layer of metal foam material of the metal foam matrix is achieved by controlling the gas release rate and cooling rate during the foam metal forming process, and specifically by accelerating the gas release rate to increase the foam porosity, and by slowly cooling to reduce the porosity of the foam metal, ultimately achieving a porosity gradient that increases step by step along the heat source direction.
4. The adsorption heat storage material with a multi-level stepped pore structure according to claim 1, characterized in that: The adsorbent coating is composed of an adsorbent, a binder and a pore-forming agent, wherein the adsorbent is one or more combinations of zeolite, silica gel, alumina and molecular sieves, the binder is one or more combinations of silica sol, aluminum sol, titanium sol, silicone resin, yellow dextrin and sesbania powder, and the pore-forming agent is one or more combinations of cellulose, nanographite sheets, ammonium bicarbonate and acrylic resin, and the components are reasonably matched to ensure the adsorption performance and structural stability of the coating.
5. The adsorption heat storage material with a multi-level stepped pore structure according to claim 1, characterized in that: The multilayer structure of the metal foam matrix adopts a step-by-step welding or brazing process, so that the combination between the layers of metal foam materials is not only physically stable, but also has good continuity in heat conduction, thereby making the heat transfer in the metal foam matrix more efficient.
6. A method for preparing the adsorption heat storage material having a multi-step pore structure according to any one of claims 1 to 5, characterized in that: The preparation method comprises at least the following steps when implemented: SS1. Preparation of metal foam matrix: Select 2 to 5 metal foam layers with different porosities, the thermal conductivity of the metal foam material in each metal foam layer is not less than 0.5 W / m·K, and arrange the selected metal foam layers from bottom to top according to the porosity from small to large to form a stepped pore structure, wherein the porosity of the bottom metal foam layer is the smallest, and its porosity is controlled in the range of 30% to 50%, and the porosity of the top metal foam layer is the largest, and its porosity is controlled in the range of 60% to 85%, and the adjacent metal foam layers are connected by welding at the interface to form a stable multilayer structure; SS2. Cleaning and drying of the metal foam substrate: The metal foam substrate prepared in step SS1 is cleaned by using an organic solvent and deionized water in combination with ultrasonic cleaning or pickling to remove impurities, oil stains and oxides attached to the surface of the metal foam substrate, and then dried at a temperature of 60 to 80° C. for 2 to 10 hours to ensure that there is no moisture and organic residue on the surface of the metal foam substrate; SS3. Preparation of adsorbent coating slurry: adsorbent, deionized water, binder and pore former are mixed into slurry in appropriate proportions, the proportion of the slurry is optimized and determined according to experimental data to ensure uniform distribution of adsorbent particles and moderate binding force between the binder and the adsorbent, wherein the adsorbent is selected from at least one of zeolite, silica gel, alumina and molecular sieve, the binder is selected from at least one of silica sol, aluminum sol, titanium sol, silicone resin, yellow dextrin and sesbania powder, the pore former is selected from at least one of cellulose, nanographite flakes, ammonium bicarbonate and acrylic resin, and the slurry is mixed and ground in a rubber mill for 1 to 3 hours to ensure that the average particle size of the slurry is controlled within the range of 30 to 50 nm; SS4. Coating of the adsorbent coating: The prepared slurry is uniformly coated on the surface of the metal foam substrate obtained in step SS2 by dipping or spraying. When the dipping process is adopted, the metal foam substrate is immersed in the slurry to ensure uniform coating of the coating. When the spraying process is adopted, the slurry is sprayed onto the surface of the metal foam substrate using a special spray gun, and the coating is formed after drying and curing at 70-90°C. The coating is applied once or multiple times until the desired coating thickness is reached, and the overall thickness of the coating is controlled to be 100-1000 μm; SS5. Calcination treatment of the adsorbent coating: The metal foam substrate coated with the adsorbent coating is calcined at a temperature of 500-600 °C for 1-6 hours to remove the organic solvent, moisture and pore-forming agent in the adsorbent coating, so as to form a multi-level pore structure containing a large number of micropores, mesopores and macropores in the adsorbent coating, thereby obtaining an adsorption heat storage material with a multi-level stepped pore structure.
7. The preparation method according to claim 6, characterized in that: In step SS1, when forming each metal foam layer, the selected metal material is heated to a molten state, and the foaming process of the molten metal, the amount of foaming agent added and the foam cooling rate are controlled to form metal foams with different porosities; and the thickness of each metal foam layer can be adjusted according to actual application requirements and controlled within the range of 10 to 50 mm, and the porosity difference between adjacent metal foam layers is controlled within the range of 5% to 15%.
8. The preparation method according to claim 6, characterized in that: In step SS2, acetone is selected as the organic solvent, and the cleaning process includes immersing the metal foam substrate in acetone and deionized water for 3 times respectively, with each immersion time being not less than 10 minutes, and ultrasonic cleaning is performed to improve the cleaning effect; the drying process is carried out in a vacuum drying oven at 60~80℃ and a pressure not higher than 0.1MPa to ensure that the moisture and organic solvent residues in the internal pores of the metal foam substrate are fully removed.
9. The preparation method according to claim 6, characterized in that: In step SS3, the mass ratio of the adsorbent, deionized water, binder and pore-forming agent is 1:1:0.1~0.2:0.02~0.1, wherein the adsorbent is 13X molecular sieve, the binder is silica sol, and the pore-forming agent is cellulose; during the slurry preparation process, the adsorbent and deionized water are first mixed and stirred for 30 minutes, and then the binder is added and stirred for 30 minutes, and finally the pore-forming agent is added and stirred evenly; after mixing to obtain the slurry, it is ground at a speed of 300~500 rpm for 2 hours to ensure the uniformity and stability of the slurry.
10. The preparation method according to claim 6, characterized in that In step SS4, the coating is carried out by spraying, using a pneumatic spray gun, the spraying pressure is controlled at 0.2~0.3 MPa, and the spraying distance is maintained at 15~20 cm; after each spraying, it is dried at 80°C for 30 minutes, and the spraying is repeated 3~5 times to achieve the desired coating thickness; after the last spraying, it is pre-cured at 85°C for 2 hours, and then post-cured at 120°C for 1 hour to ensure the bonding strength between the coating and the metal foam substrate; the final thickness of the coating is controlled at 300±50 μm.
Citation Information
Patent Citations
High heat-conduction and high thermal-radiation sheet and preparation method thereof
CN108172554A
Foam metal supporting adsorption material and preparation method thereof
CN113117647A
Photo-thermal integrated phase change heat storage device based on stepped three-period extremely-small-curved-surface porous foam
CN118896511A
Heat sink and fabricating method the same using metalfoam
KR1020080032324A
Adsorption-desorption apparatus and process
US20120006193A1
Cited By
Tritium-compatible cryopump cold plate, preparation method thereof and tritium-compatible cryopump
CN120867987A
Trace gaseous substance detection method, thermal desorption preconcentrator and preparation method of thermal desorption preconcentrator
CN121695834A
Methods for detecting trace gaseous substances and preparation of thermal desorption pre-concentrator
CN121695834B